Leif and the Fall - Grant, Allison Sweet; Grant, Adam M.; Liddiard, Merrilee (New York : Dial Books for Young Readers, 2020)
Leif is a leaf who is worried about autumn and having to fall, so, with his friend Laurel, he uses the resources around him to create a net, a kite, and a parachute in hopes of softening his landing.
Keywords: Anxiety -- Fiction; Leaves -- Fiction; Autumn -- Fiction; Fear -- Fiction; Failure (Psychology) -- Fiction; Persistence -- Fiction; Anxiety; Autumn; Children and death; Failure (Psychology); Inventors; Leaves; Persistence; Picture books; Fiction; Juvenile works; Picture books